2010
DOI: 10.1186/1742-2094-7-87
|View full text |Cite
|
Sign up to set email alerts
|

CCL2/CCR2 and CX3CL1/CX3CR1 chemokine axes and their possible involvement in age-related macular degeneration

Abstract: The causes of age-related macular degeneration (AMD) are not well understood. Due to demographic shifts in the industrialized world a growing number of people will develop AMD in the coming decades. To develop treatments it is essential to characterize the disease's pathogenic process. Over the past few years, numerous studies have focused on the role of chemotactic cytokines, also known as chemokines. Certain chemokines, such as CCL2 and CX3CL1, appear to be crucial in subretinal microglia and macrophage accu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
74
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(79 citation statements)
references
References 63 publications
3
74
0
Order By: Relevance
“…[7][8][9]20 In this study, we showed that light exposure also affected the RPE in vivo, by promoting ROS induction.…”
Section: Discussionmentioning
confidence: 55%
“…[7][8][9]20 In this study, we showed that light exposure also affected the RPE in vivo, by promoting ROS induction.…”
Section: Discussionmentioning
confidence: 55%
“…18,19 Mice with perturbed signaling of CCR2 and CX 3 CR1, two of the major chemokine receptors involved in monocyte recruitment, demonstrate retinal alterations that recapitulate some of the features of AMD. [20][21][22][23] Furthermore, studies have recently shown that several of the chemokine ligands, including CCL2 (the ligand for CCR2, also known as MCP-1, or monocyte chemoattractant protein 1), are present in higher intraocular concentrations in NV-AMD eyes 24 and urine. 25 High levels of CCL2 have been found in RPE in vivo, 26 and this chemokine may be associated with CNV growth in mice.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to PRRs, various other molecules are also involved in microglial activation. Fractalkine (CX3CL1) is constitutively produced by neurons in the CNS, 4,5 including the neural retina, [6][7][8] whereas its receptor CX3CR1 is exclusively expressed by microglial cells. 5,8,9 CX3CL1-CX3CR1 signaling is one of the main pathways involved in neuronmicroglia interactions and plays a crucial role in regulating microglial activation.…”
Section: Discussionmentioning
confidence: 99%